Antimutagenic and antioxidant activity of novel 4-substituted phenyl-2,2'-bichalcophenes and aza-analogs - El-Sayed WM; Hussin WA (Dove Medical Press, 2013)
Wael M El-Sayed,1,2 Warda A Hussin31King Faisal University, Faculty of Science, Departments of Biological Sciences and Chemistry, Al-Hufof, Ahsa, Kingdom of Saudi Arabia; 2University of Ain Shams, Faculty of Science, Department of Zoology, Cairo, Egypt; 3Al-Azhr University, Faculty of Science, Department of Botany and Microbiology, Cairo, EgyptAbstract: Evaluation of the potential antimutagenic activities of new compounds by Ames assay has been of great interest for the development of novel therapeutics for many diseases including cancer. Ten novel bichalcophenes with in vitro and in vivo broad spectrum activities against various microbial strains were investigated throughout the present study for their cytotoxic, antioxidant, and antimutagenic potential in a Salmonella reverse mutation assay system against sodium azide (NaN3) and benzo[a]pyrene (B[a]P). At nontoxic concentrations, all bichalcophenes alone or in combination with NaN3 (1 µg/plate) or B[a]P (20 µM) with S9 mix were not mutagenic. The bichalcophenes significantly reduced NaN3- and B[a]P-induced mutagenicity under pre-exposure and co-exposure conditions in a concentration-independent manner. However, the antimutagenic activity of bichalcophenes against B[a]P varied depending on the exposure regimen, being more effective under pre-exposure conditions. The antimutagenic activity was correlated with a high antioxidant activity that could promote the DNA repair system. Bichalcophenes are least likely to interfere with the microsomal bioactivation of B[a]P. Monocationic bichalcophenes were superior to the corresponding mononitriles as antimutagenic agents against both mutagens investigated, possibly due to the higher nucleophilic centers they have which could bind and protect the bacterial DNA. Three monocationic compounds were shown to have a strong anticancer activity against the 58 cell line. Based on the results of the present investigation, monocationic compounds (1, 4, and 5B) will be selected for further time consuming and costly chemoprevention studies in animal models.Keywords: bichalcophenes, Salmonella typhimurium, sodium azide, benzo[a]pyrene, antimutagenicity